(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article explores the use of various innovative methods in the process of teaching construction terms in foreign languages in the example of Russian language, to improve the communicative competencies and communication skills of students of non-linguistic faculties of the university. The article discusses improving the level of language competence and cognitive activity of students, improving the quality of language training of specialists and their needs in learning a foreign language.